Um hermeneuta da morte: José Saramago na literatura e na história - Santos, Nataly Yolanda Capelari dos (2019)
Death at intervals (2005), by José Saramago, talks about the problem of death and tries to understand the final issues, and all the others raised. The book suggests a deep reflection about death, talking about life, starting from a metaphorical reading about death, which is transformed into a character. With this in mind, the study analyzes Saramago's novel according to Edgar Morin's Paradigm of Complexity which considers the opposites in their peculiarities, without excluding them, understanding that they are part of a larger whole. We move like the novel, by the order and disorder of a life without death and a death without life. We try to understand how the writer talks about death, through life, and what resources are used for it, how he constructs the main character, reviving in our imaginary the historical and personal knowledge we have of death for after modify it and demystify some taboos and understandings through literature. For this, we are based on the understanding of the time and space of the writer, the narrative, the reader and the researcher as influencers and interferers in the literary production, supported by Harvey, Bauman, Flory and Foucault. We also search in history for understanding what death is and how it was represented, according to Certeau, Morin, Elias and Àries. We study how history and reality are drawn into fiction, working together through language based on Compagnon, Candide, Benjamin, Bakhtin, Ricoeur, Pesavento, and Flory’s survey. We study and dismember the Saramaguian novel in order to understand and identify how José Saramago transforms into the hermeneutic of death, transiting through Literature and History.